Efficacy of gallium maltolate against Lawsonia intracellularis infection in a rabbit model. Issue 6 (15th April 2014) - Sampieri, F.; Allen, A. L.; Alcorn, J.; Clark, C. R.; Vannucci, F. A.; Pusterla, N.; Mapes, S. M.; Ball, K. R.; Dowling, P. M.; Thompson, J.; Bernstein, L. R.; Gebhart, C. J.; et al.
<x xml:space="preserve">Abstract</x> Antimicrobial efficacy against Lawsonia intracellularis is difficult to evaluate in vitro, thus, the effects of gallium maltolate's (GaM) were investigated in a rabbit model for equine proliferative enteropathy (EPE). Juvenile (5–6‐week‐old) does were infected with 3.0 × 108L. intracellularis/rabbit and allocated into three groups (n = 8). One week postinfection, one group was treated with GaM, 50 mg/kg; one, with doxycycline, 5 mg/kg; and one with a sham‐treatment (control). Feces and blood were collected daily and weekly, respectively, to verify presence of L. intracellularis fecal shedding using qPCR, and seroconversion using immunoperoxidase monolayer assay. Rabbits were sacrificed after 1 week of treatment to collect intestinal tissues focusing on EPE‐affected sections. Intestinal lesions were confirmed via immunohistochemistry. No difference was noted between treatments regarding EPE‐lesions in jejunum (P = 0.51), ileum (P = 0.74), and cecum (P = 0.35), or in L. intracellularis fecal shedding (P = 0.64). GaM and doxycycline appear to have similar efficacy against EPE in infected rabbits.